Parking ‘didacticiel’: a game-based learning application of vehicle parking - Mohamed, Juliana; Ahmed, Mohamad Baharin; Mohammad Faiz Marzuki; Adnan, Muhammad Izzat; Md. Mokhtar Ashari, Muhammad Farees Firdaus @ Md. Firdaus (Multidisciplinary Applied Research and Innovation, 2021)
Parking lot area can be so difficult to a certain people who tried to park exactly in the parking lot. Parking ‘didacticiel’, a game-based learning application, develop to teach users about road rules and how to be parking properly in a very attractive way by 3D modelling. ADDIE model has been used to develop the application including the standard from Road Transport Department Malaysia (JPJ). The application educates driver especially to the candidates from driving school center by recognize the right signs on the road. In future, the improvement of the application will be discovered by the development of virtual reality game-based learning using a goggle.